Collaborative Governance pada Layanan 112 untuk Mewujudkan Respon Cepat pada Pengaduan Darurat di Kota Surabaya - Andini Salsabilla; Adi Soesiantoro; Ghulam Maulana Ilman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Emergency complaint services are a critical component of public service delivery, requiring speed, coordination, and integration across multiple agencies. The Surabaya City Government developed Command Center 112 as an innovative public service initiative to respond to emergency incidents quickly and in a coordinated manner. This study aims to analyze the implementation of Collaborative Governance in the management of the Command Center 112 service in Surabaya, using the model by Ansell and Gash, which includes four key indicators: starting conditions, institutional design, facilitative leadership, and the collaborative process. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings reveal that collaboration among government agencies, volunteers, and the community has been built functionally and adaptively through regulatory support, standard operating procedures (SOPs), and open communication among stakeholders. However, challenges remain in the form of public perceptions regarding service response quality, which has not been uniformly experienced. These results highlight the importance of strengthening public communication and increasing community involvement in service evaluation. Overall, Command Center 112 in Surabaya serves as a successful example of Collaborative Governance implementation in urban emergency complaint services.